Honey Bee Diversity Is Swayed by Migratory Beekeeping and Trade Despite Conservation Practices: Genetic Evidence for the Impact of Anthropogenic Factors on Population Structure - Kükrer, Mert; Kence, Meral; Kence, Aykut (Frontiers in Ecology and Evolution, 2021)
The intense admixture of honey bee (Apis mellifera L.) populations at a global scale is mostly attributed to the widespread migratory beekeeping practices and replacement of queens and colonies with non-native races or hybrids of different subspecies. These practices are also common in Anatolia and Thrace, but their influence on the genetic make-up of the five native subspecies of honey bees has not been explored. Here, we present an analysis of 30 microsatellite markers from honey bees from six different regions in Anatolia and Thrace (N = 250 samples), with the aim of comparing the impact of: 1) migratory beekeeping, 2) queen and colony trade, and 3) conservation efforts on the genetic structure of native populations. Populations exposed to migratory beekeeping showed less allegiance than stationary ones. We found genetic evidence for migratory colonies acting as a hybrid zone mobile in space and time, becoming vectors of otherwise local gene combinations. The effect of honey bee trade leaves very high introgression levels in native honey bees. Despite their narrow geographic range, introgression occurs mainly with the highly commercial Caucasian bees. We also measured the direction and magnitude of gene flow associated with bee trade. A comparison between regions that are open and those closed to migratory beekeeping allowed the evaluation of conservation sites as centers with limited gene flow and demonstrated the importance of establishing such isolated regions. Despite evidence of gene flow, our findings confirm high levels of geographically structured genetic diversity in four subspecies of honey bees in Turkey and emphasize the need to develop policies to maintain this diversity. Our overall results are of interest to the wider scientific community studying anthropogenic effects on the population diversity of honey bees and other insects. Our findings on the effects of migratory beekeeping, queen and colony replacements have implications for the conservation of honey bees, other pollinators, and invertebrates in general and are informative for policy-makers and other stakeholders in Europe and beyond.